Phenylpropanoids in Agastache foeniculum and Its Cultivar A. foeniculum ‘Golden Jubilee’ - Tae Park, Woo; Hoon Kim, Haeng; Cheon Chae, Soo; Woong Cho, Jin; Un Park, Sang (Asian Journal of Chemistry, 2014)
The present study describes the level of phenylpropanoids in the organs (leaf, flower, stem and root) of Agastache foeniculum and its cultivar Agastache foeniculum 'Golden Jubilee.' Analysis confirmed the presence of 3 different phenylpropanoids i.e., rosmarinic acid, tilianin, and acacetin. Rosmarinic acid accumulation was higher in the roots of both species, it being 6.3, 4.3 and 11.3 times higher in the roots of A. foeniculum 'Golden Jubilee compared to the flower, leaf and stem, respectively of the same. Tilianin accumulation was higher in all 'Golden Jubilee' organs compared to A. foeniculum; in particular, the Golden Jubilee flower contained 50 times more tilianin compared to the root of A. foeniculum. Tilianin was not detected in the stem of A. foeniculum. Acacetin accumulation was lower in the various plant parts of both A. foeniculum compared to other phenylpropanoids, even though the greatest amount of acacetin was accumulated in the flower. The findings of this study indicate that the flower and root of A. foeniculum, particularly the cultivar Golden Jubilee, might be important for higher rates of phenylpropanoid production, which are of high medicinal value.